Evaluation of clinical efficacy and safety of cervical trauma collars: differences in immobilization, effect on jugular venous pressure and patient comfort - Karason, Sigurbergur (BioMed Central, 2014)
BACKGROUND: Concern has been raised that cervical collars may increase intracranial pressure in traumatic brain injury. The purpose of this study was to compare four types of cervical collars regarding efficacy of immobilizing the neck, effect on jugular venous pressure (JVP), as a surrogate for possible effect on intracranial pressure, and patient comfort in healthy volunteers. METHODS: The characteristics of four widely used cervical collars (Laerdal Stifneck® (SN), Vista® (VI), Miami J Advanced® (MJ), Philadelphia® (PH)) were studied in ten volunteers. Neck movement was measured with goniometry, JVP was measured directly through an endovascular catheter and participants graded the collars according to comfort on a scale 1–5. RESULTS: The mean age of participants was 27 ± 5 yr and BMI 26 ± 5. The mean neck movement (53 ± 9°) decreased significantly with all the collars (p < 0.001) from 18 ± 7° to 25 ± 9° (SN < MJ < PH < VI). There was a significant increase in mean JVP (9.4 ± 1.4 mmHg) with three of the collars, but not with SN, from 10.5 ± 2.1 mmHg to 16.3 ± 3.3 mmHg (SN < MJ < VI < PH). The grade of comfort between collars varied from 4.2 ± 0.8 to 2.2 ± 0.8 (VI > MJ > SN > PH). CONCLUSION: Stifneck and Miami J collars offered the most efficient immobilization of the neck with the least effect on JVP. Vista and Miami J were the most comfortable ones. The methodology used in this study may offer a new approach to evaluate clinical efficacy and safety of neck collars and aid their continued development.